Seroprevalensi, Pengetahuan, dan Sikap Preventif Hepatitis B Virus (HBV) Pada Mahasiwa Ahli Teknologi Laboratorium Medik di Surakarta - Rumeyda Chitra Puspita; Lucia Sincu Gunawan (Biomedika, 2019)
Health workers, especially students of the Medical Laboratory Technology (MLT) have a greater risk of contracting hepatitis B virus infection from exposure to body fluids when doing clinical labs. The importance of seroprevalence, knowledge and attitudes greatly influences students when doing practicum as a preventive measure for hepatitis B infection. This study aims to identify MLT student’s seroprevalence, knowledge and preventive attitudes towards hepatitis B virus infection. This research is a quantitative descriptive study using a cross-sectional study design carried out in one of the health universities in Surakarta in October - November 2018. Subjects were taken using total sampling techniques with a total of 71 students study in D-IV Medical Laboratory Technology. Data collection was done by questionnaire about knowledge, and preventive attitude of hepatitis B infection in students and blood samples collected and screened with HBsAg examination. Data analysis using computerization with SPSS version 21. The results showed that MLT students had good knowledge of 80.3%, good preventive attitudes of 97.2%, and seroprevalence of 1.4% of students with positive HBsAg. Knowledge and preventive attitudes of MLT students fall into the good category. Seroprevalence of D-IV MLT students showed poor results. It is expected that the higher education institution to carry out HBsAg examination as a college entry requirement, so that it can reduce work risks and can improve work safety as medical personnel.